2003
DOI: 10.1007/s10295-003-0054-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vitreoscilla hemoglobin on the 2,4-dinitrotoluene (2,4-DNT) dioxygenase activity of Burkholderia and on 2,4-DNT degradation in two-phase bioreactors

Abstract: Expression of vgb, encoding Vitreoscilla hemoglobin (VHb), in Burkholderia strain YV1 was previously shown to improve cell growth and enhance 2,4-dinitrotoluene (2,4-DNT) degradation compared with control strain DNT, especially under hypoxic conditions. In the work reported here, the ratio of 2,4-DNT degraded to oxygen uptake was approximately 5-fold larger for strain YV1 than for strain DNT. The addition of purified VHb to cytosolic fractions of strain DNT increased 2,4-DNT degradation 1.5-fold, compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 46 publications
(56 reference statements)
0
22
1
Order By: Relevance
“…Burkholderia strain DNT is an aerobic bacterium known to degrade a wide range of both aliphatic and aromatic toxic organic chemicals such as trichloroethylene (TCE), trinitrotoluene (TNT) and 2,4-DNT [Haigler et al, 1996;Munakata-Marr et al, 1996;Spanggord et al, 1991;Suen and Spain, 1993;Suen Growth was in shake flasks, except in the case of the Lin et al [2003] experiments, which were run in two-phase bioreactors. Burkholderia is Burkholderia strain DNT.…”
Section: Initial Small-scale Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Burkholderia strain DNT is an aerobic bacterium known to degrade a wide range of both aliphatic and aromatic toxic organic chemicals such as trichloroethylene (TCE), trinitrotoluene (TNT) and 2,4-DNT [Haigler et al, 1996;Munakata-Marr et al, 1996;Spanggord et al, 1991;Suen and Spain, 1993;Suen Growth was in shake flasks, except in the case of the Lin et al [2003] experiments, which were run in two-phase bioreactors. Burkholderia is Burkholderia strain DNT.…”
Section: Initial Small-scale Studiesmentioning
confidence: 99%
“…Further studies with the Burkholderia system showed that the VHb-related enhancement occurs in a variety of media, and is relatively greater under hypoxic compared with higher aeration conditions [Nasr et al, 2001]. This work was followed by experiments demonstrating a direct stimulation by VHb of the first enzyme in the Burkholderia DNT catabolic pathway, perhaps due to direct delivery of oxygen from VHb to this oxygenase [Fish et al, 2001;Lee et al, 2004;Lin et al, 2003]. At the same time, the initial genetic engineering experiments, which had all been done using vgb carried on plasmid pSC160 [Liu et al, 1995], were extended to show that vgb could be stably integrated into the host chromosome and result in the same enhancement of aromatic compound degradation [Chung et al, 2001;Kim et al, 2005].…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that the beneficial effects in bacteria are the result of direct interaction of VHb with the terminal respiratory oxidase, delivering oxygen to it to enhance oxidative phosphorylation and thus the production of ATP [16,30,32]. In the case of bioremediation enhancement, a direct delivery of oxygen by VHb to oxygenases which degrade aromatics may occur [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were previously observed in the degradation of 2,4-dinitrotoluene (2,4-DNT), which was catalyzed by dioxygenase in Burkholderia spp. (10). Moreover, the Dsz enzymes are soluble and found in the cytoplasm (5,9).…”
mentioning
confidence: 99%